FORMS OF DISPLAY OF MORAL SHAME: SYSTEM ANALYSES - Турчин, М. Я. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article investigates the features of shame as polyphonic moral sense. The system analyses of the forms of display of shame are implemented, starting from elementary decency and ending a shame as the highest degree of public condemnation of immoral acts. The measure and the extremes are comprehended in the process of description of value of moral shame for a person and society.